Perencanaan Angkutan Khusus Mahasiswa Universitas Pendidikan Nasional - Putri, Dewa Ayu Putu Adhiya Garini; Freitas, Lelia Petronila Gusmao (Universitas Ibn Khaldun, 2026)
The National Education University (Undiknas) Denpasar Bali, is facing transportation challenges due to the increasing number of students, consisting of 6,592 students. The high use of private vehicles by 43% of students causes traffic jams and environmental degradation around the campus. To overcome this problem, good transportation planning is needed, including the provision of campus buses. This research analyzes student characteristics, determines routes, analyzes special transportation operational systems and vehicle operational costs. Methodology This study uses quantitative and descriptive methods with primary and secondary data. Of the potential students who agree to move using special transportation, 95% agree and 5% disagree. This special transportation uses one route, namely: Jl. Sunset road – Jl. Bypass Ngurah Rai – Jl. Diponogoro – Jl. Raya Sesetan – Jl. Sidakarya – national educational university with a distance of 19.7 km. Special transportation operates with mini buses that can accommodate 16 people with operating times running from 08.00 WITA to 17.00 WITA. With a planned speed of 40 km/hour, travel time 30 minutes, circulation time 69 minutes, number of routes = 7, headway 30 minutes and number of vehicles = 3 vehicles. And the analysis that has been carried out shows that the vehicle operating costs on the student route (Route I) are Rp. 18,719,525 per vehicle/km.